Maison Méditerranéenne des Sciences de l'Homme - Maison Méditerranéenne des Sciences de l'Homme (2014)
A place of living memory, the Phonotheque of the MMSH aims to bring together recordings of the sound heritage that have the value of ethnological, linguistic, historical, musicological or literary information on the Mediterranean area. It documents fields little covered by conventional sources, or completes them with the point of view of actors or witnesses. The collection holds more than 8000 hours of audio archives recorded since the late 1950s concerning all the humanities sciences.